Paul, the Spirit, and the People of God - Fee, Gordon Donald, 1934- (Peabody, MA Hendrickson, 1996)
Includes bibliographical references and index.
Keywords: Holy Spirit -- biblical teaching; Bible. N.T. Epistles of Paul -- theology